1989
DOI: 10.1073/pnas.86.1.162
|View full text |Cite
|
Sign up to set email alerts
|

Detection of genes with a potential for suppressing the transformed phenotype associated with activated ras genes.

Abstract: Seven morphologically nontransformed (flat) revertants with reduced tumorigenicity in vivo have been isolated from populations of Kirsten sarcoma virus-transformed NIH 3T3 cells transfected with a cDNA expression library ofnormal human fibroblasts. Each revertant harbors 1-10 recombinant plis per cell and retains a rescuable transforming virus as well as high level expression of v-Ki-ras-specific RNA and the viral oncogene product, p21v-i-. Transformed phenotypes are suppressed in cell hybrids generated by fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
62
0
4

Year Published

1990
1990
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(67 citation statements)
references
References 21 publications
1
62
0
4
Order By: Relevance
“…Di erent p70 expressors grew to densities between 6610 4 and 1610 5 cells/cm 2 , while the control transfectants achieved densities of at least 2.5610 5 cells/cm 2 . The saturation density of the p70 expressors was similar to that of contact-inhibited NIH3T3 cells, which typically grow to approximately 1610 5 cells/ cm 2 (Noda et al, 1989). Despite the di erence in saturation density, the initial growth rate of the p70 expressing clones was only slightly slower than that of a b c d Figure 5 Actin organization in NIH3T3-OFF cells and ST5-p70 expressing transfectants.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Di erent p70 expressors grew to densities between 6610 4 and 1610 5 cells/cm 2 , while the control transfectants achieved densities of at least 2.5610 5 cells/cm 2 . The saturation density of the p70 expressors was similar to that of contact-inhibited NIH3T3 cells, which typically grow to approximately 1610 5 cells/ cm 2 (Noda et al, 1989). Despite the di erence in saturation density, the initial growth rate of the p70 expressing clones was only slightly slower than that of a b c d Figure 5 Actin organization in NIH3T3-OFF cells and ST5-p70 expressing transfectants.…”
mentioning
confidence: 77%
“…The commercially available NIH3T3-OFF line was designed to give inducible expression of proteins placed under the control of a tetracycline sensitive activator protein (Clontech, Palo Alta, CA, USA). This line contained a homogenous population of refractile cells which grew to a considerably greater density than that reported for NIH3T3 (Noda et al, 1989) and displayed some characteristics of the transformed phenotype, including a refractile morphology and high-density growth. In addition, they contained little if any p70 (Figure 3a, lane 1), while NIH3T3 cells contained readily detectable p70 (lane 2).…”
mentioning
confidence: 83%
“…RECK was first isolated as a transformation-suppressor gene by cDNA expression cloning (Noda et al, 1989;Takahashi et al, 1998) and found to encode a membraneanchored regulator of several extracellular metalloproteinases, including MMP2, MMP7, MMP9, MT1-MMP, ADAM10 and CD13 (Takahashi et al, 1998;Oh et al, 2001;Miki et al, 2007;Muraguchi et al, 2007;Omura et al, 2009). These proteases have been implicated in tissue remodeling and cleavage of various extracellular molecules under normal and pathological conditions (Sternlicht and Werb, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This, together with the observation that Rap1, when overexpressed, can reverse the K-Ras transformed phenotype of NIH3T3 cells , has led to the hypothesis that Rap1 could be a possible antagonist of Ras. Several studies indeed showed this antagonistic action of Rap1 on a variety of Ras-dependent responses and possibly also in the sevenless signal transduction pathway (for references see Bokoch, 1993;Noda, 1993). Despite this, a reversal of the transformed phenotype in a variety of human tumor cell lines upon expression of Rap1A was not observed (Sato et al, 1994).…”
Section: Introductionmentioning
confidence: 99%